Health Requirements For LGBTIQ+ Refugees - Gizem Beycan Etkili; Emel Öztürk Turgut; Ayşegül Dönmez (Dokuz Eylul University, 2021)
Where conflicts often turn to aggression, the heaviest losses are primarily in groups that need support, such as women and children, while the LGBTIQ+ population is among these vulnerable groups. Like other groups outside the boundaries that society accepts as 'normal', LGBTIQ+ population are struggling for their basic human rights, while potential risks are getting stronger if they are under a war and refugee conditions where continuity of life is threatened. Today, Turkey has opened its border crossing about four million war victimized Syrian, and maintains the role as one of the most important countries that provides refugee and life safety support to them. Nurses are at the forefront of healthcare system and play a key role in this challenge, as they are organizers of this service, as well as their roles of educator and advocate. Also, Turkey can be considered as an important partner of this struggle for the LGBTIQ+ population. This review's aimed to investigate the health care needs of LGBTIQ+ refugees with a physical and psychosocial approach, who had to leave their countries due to the war. In according to view of Syrian LGBTIQ+ refugees in Turkey, LGBTIQ+ refugees' general health requirements will be shed light on and suggestions were presented for the practices of nursing discipline, which is the primary force of the healthcare team.